Parallel corpora and contrastive linguistics: Where to look for pitfalls in the translation of information structure - Dušková, Libuše (Bergen Language and Linguistics Studies, 2018)
This paper deals with some of the problems encountered in English-Czech contrastive studies of information structure based on parallel texts. It <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: SV; mso-fareast-language: SV; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Courier New';" lang="SV">largely focuses on those arising from the different hierarchy of the respective word order principles, the primary one being grammatical function in English, and information structure / functional sentence perspective (FSP) in Czech. Three aspects are considered: linear ordering of clause elements, FSP structure, and the basic distribution of communicative dynamism. Owing to the character and complexity of the FSP factors, word order, context, semantics and intonation, and the lack of distinctive realization forms of the carriers of the FSP functions, the study is based on manual excerpts from passages of digitalized running text of three English novels and their Czech translations drawn from the InterCorp. The results show that most problems arise in the case of different linear ordering as it may indicate either an identical or a different FSP structure.